Antagonistic Activity of the Endophy Fungi of Lime Plant (Citrus Aurantifolia) on Candida Albicans - Aji, Oktira Roka; Wahyuni, Sri (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This study aims to isolate and determine the antagonistic activity of lime's endophytic mushrooms on Candida albicans. Antagonism tests were performed in vitro with dual culture methods. The study obtained 14 isolates that were successfully isolated from the stem, roots, leaves, and peels of lime fruit. A total of 8 isolates could inhibit Candida albicans through antibiosis mechanisms and healthy competition. The isolates with the highest inhibition percentage were KD2 and MA1 (42.85%).